1983
DOI: 10.1063/1.446313
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemistry in Fock space. II. Effective Hamiltonians in Fock space

Abstract: The concept of an effective Hamiltonian in Fock space is introduced. It is based on the division of the entire one-particle space into subspaces of ‘‘active’’ and ‘‘inactive’’ orbitals. The effective Fock space Hamiltonian has—for active model states—the same eigenvalues as the full Hamiltonian. The theory outlined in this context differs from that of paper I mainly in a different definition of the ‘‘diagonal part’’ of an operator, and in the fact that the ‘‘quasidegenerate case’’ applies throughout. The separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(65 citation statements)
references
References 40 publications
0
65
0
Order By: Relevance
“…[129][130][131] ). Using a broad definition of diagonality is ill-advised because we must avoid to induce strong in-medium 3N, .…”
Section: Imsrg Decoupling In the Single-reference Casementioning
confidence: 99%
“…[129][130][131] ). Using a broad definition of diagonality is ill-advised because we must avoid to induce strong in-medium 3N, .…”
Section: Imsrg Decoupling In the Single-reference Casementioning
confidence: 99%
“…"Alternative" CC methods have been proposed, including extended coupled cluster 34 (ECC), quadratic coupled cluster 35 (QCC), improved coupled cluster 36 (ICC), unitary coupled cluster [37][38][39][40] (UCC), and variational coupled cluster 41 (VCC), and a number of studies 20,[28][29][30][31][32][33] have confirmed the superiority of VCC and related approaches over TCC for the treatment of problems involving strong static correlation. This can be attributed to the upper bound property of VCC, which ensures that calculated VCC energies are always higher than FCI energies, which is not the case for TCC.…”
Section: Introductionmentioning
confidence: 99%
“…(1) for n energy levels. In (8), H'ff is an effective Hamiltonian defined in the n-dimensional model space and CR is the corresponding wave operator acting on the right in the model space. H ' f f is chosen in such a way that the n solutions of H'ff in the model space are the projection in this space of n exact solutions of H. Within such a choice, R obeys…”
Section: The Bloch Effective Hamiltonianmentioning
confidence: 99%